AUTOMATED DETECTION OFWBC CANCER USING ADVANCED IMAGE ENHANCEMENT ALGORITHMS AND IOT - Reddy, B. Hemanth; Subitha, D. (International Journal of Psychosocial Rehabilitation, 2020)
Leukemia is a sort of malignant growth that creates in blood tissues and delivers irregular molded white platelets by activating fast creation. This sickness is the most widely recognized perilous one for the two people. Consequently diagnosing this infection is viewed as the well creating territory where best strategies are required. Right now propose a model that sends the message in his/her cell phone about the status of disease (regardless of whether it is Benign or Malignant tumor). The proposed model procedures the picture stacked in the PC utilizing picture upgrade, division and highlight extraction calculations. At that point it is imparted to the client or attender cell phone through the Wi-Fi module by methods for IOT. In future, the proposed module, we are supplanting the current picture improvement calculation by the propelled calculations to upgrade the quality and speed.